DAYA SAING SDM KEWIRAUSAHAAN DI ERA DIGITAL: MENGINTEGRASIKAN LITERASI DIGITAL, KREATIVITAS, DAN SOLUSI INOVATIF - Dika Argiyan Syah; Fiqih Maria Rabiatul Hariroh; Adibah Yahya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research aims to analyse the influence of digital literacy, creativity, and innovative solutions on the competitiveness of human resources (HR) in entrepreneurship in the digital era. The main issue raised is the low readiness of HR in entrepreneurship to strategically utilise digital technology. The research method employs a quantitative approach, with a population and sample of 100 people using the soft modeling characteristics of SmartPLS. The analysis results indicate that digital literacy, creativity, and innovative solutions have a significant impact on the competitiveness of HR.